Sectores populares y "delitos leves" en la ciudad de México a mediados del siglo XIX - Teitelbaum, Vanesa E. (El Colegio de México, A.C., 2006)
This text explores the transgressions committed by popular sectors while also examining their resistance of the control and coercion of the state. It studies the arrests of individuals from popular sectors by police officers in the mid-19th Century and their subsequent trials. These documents show that, rather than dealing with serious crime, many of these arrests reflected the social tensions and conflicts faced by citydwellers on an everyday basis. In particular, the economic pressures on popular sectors in the mid-19th Century led many to turn to theft and other activities outside of legal channels.